Operation and output pulse characteristics of an extremely compact capillary-discharge tabletop soft-x-ray laser - Benware, B. R., author; Burd, D. J., author; Moreno, C. H., author; Rocca, Jorge J., author; Optical Society of America, publisher (Colorado State University. Libraries, 1997)
We report on the operating parameters and laser output pulse characteristics of an extremely compact discharge-pumped 46.9-nm laser of a size comparable with that of many widely utilized visible and ultraviolet gas lasers. This capillary-discharge laser generated subnanosecond laser pulses with energies of as much as 25 μJ by single-pass amplification in an 18.6-cm-long argon-plasma column. Measurements of the laser output energy, pulse width, far-field beam profile, and beam divergence are reported.